Findings from Focus Groups Indicating what Chinese American immigrant women think about breast cancer and breast cancer screening - Lee-Lin, Frances (2012)
OBJECTIVES: To explore beliefs of Chinese American, immigrant women related to breast cancer and mammography. DESIGN: Qualitative description with semi-structured focus groups. SETTING: Metropolitan Portland, Oregon. PARTICIPANTS: Thirty eight foreign-born Chinese women, age 40 and older, in five focus groups. METHODS: Focus group discussions in Chinese were audio taped, transcribed, and translated into English. Using a process of directed content analysis, group transcripts were coded for themes based on the discussion guide. RESULTS: Three main themes emerged from the analysis: knowledge and beliefs; support, communication, and educational needs; and access to care. Subthemes included beliefs such as barriers and facilitators to screening and perceptions about personal breast cancer risk. Several women were profoundly affected by the negative breast cancer-related experiences of relatives and friends. Some common myths remain about causes and treatment of breast cancer. CONCLUSIONS: Although Chinese American immigrant women share beliefs with other minority women in the United States, some culturally-related barriers such as alienation due to cultural reasons for not sharing diagnosis with anyone and beliefs about the efficacy of Eastern versus Western medicine may affect adherence to screening and treatment. Facilitators included being told to get the test and getting screened for the sake of the family, while erroneous information about the cause of breast cancer such as diet and stress remained. Primary care providers such as advanced practice nurses should take into account culturally driven motivations and barriers to mammography adherence among Chinese American immigrant women. Provider-client interactions should involve more discussion about women’s breast cancer risks and screening harms and benefits. Such awareness could open a dialogue around breast cancer that is culturally sensitive and non-threatening to the patient. Information may need to be tailored to women individually or targeted to sub-ethnic groups rather than using generic messages for all Asian immigrant women.